Pembuktian Sederhana Dalam Putusan Pailit (Studi Kasus Perkara Nomor 515 K/PDT.SUS/2016) - Iwan Sidharta (Fakultas Hukum Universitas Pancasila, 2018)
The interpretation of simple proofing in bankruptcy petition hearings is often interpreted differently, both by the panel of judges and experts. Those different interpretations affect such kind of legal uncertainty and injustice for litigant parties. To exam simple proofing matter, this study uses normative legal research method. Based on this study could be known that simple proofing process in bankruptcy petition cases is often interpreted differently by the panel of judges, whereas Article 8 paragraph (4) of the Bankruptcy Act and the Postponement of Debt Payment Obligations are clear enough wants to reach legal certainty, justice, and expediency. In the case of Decision Number 515 K/PDT.SUS/2016, the judges argued that the simple evidentiary requirements as proposed by the debtor bankruptcy petitioner are not simple, even though the bankruptcy petitioner has proven and postulate that there are 2 or more corporate creditors and salary arrears for employees whose value reaches Rp 3 billion as a proof of condition as according to Article 2 paragraph (1) of the Bankruptcy Act. The judges believes that salary payable to employees could make the proofing requirements not simple, while the Bankruptcy Act clearly states that if the debtor has two or more creditors and does not pay in full at least one debt that has matured and can be billed, debtor could be declared bankrupt by court decision, either upon his own application or because of the request from one or more of his creditors.